Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Highschoolcheerleader

  • 4 years ago

how do you solve 12=-4(-6x-3)

  • This Question is Closed
  1. .Sam.
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    12=-4(-6x-3) -4(-6x-3)=12 -(-6x-3)=3 6x+3=3 6x=0 x=0

  2. mubzz
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    You first solve the parenthesis towards the right side of the '=' This will give you your first step, i.e. 1) 12 = (-4*-6x) - (3*-4) [remember that two negatives multiplied give a positive] 2) 12 = 24x +12 [you now move the '12' on the right side to the left side of the equation] 3] 12 -12 = 24x 4) 0 = 24x x= 0 Answer

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy